Carbon nanofiber dispersion in alkali solution and its reinforcement of alkali-activated volcanic ash-based geopolymers - Yue Hou (Journal of Cleaner Production, 2023)
Volcanic ash has several negative impacts on the environment and can be used in massive to synthesize geopolymers, which are considered quasi-brittle. Carbon nanofibers (CNFs) can reinforce the geopolymers, and the dispersion of CNFs directly determines the reinforcement effect. However, the dispersion of CNFs in alkali solutions is challenging. In this paper, the effect of surfactant type, dosage, and ultrasonic time on CNFs dispersion in aqueous and alkali solutions was investigated by the quantitive method of microscopic image processing to determine the preferred dispersion scheme. Zeta potential tests and visual observation were used to analyze the mechanism and stability. Based on this, volcanic ash-based geopolymer nanocomposites with 0.1 wt% contents of CNFs were synthesized. The mechanical properties were tested, and the microstructure was characterized using Scanning Electron Microscope coupled with Energy Dispersive Spectroscopy and Mercury Intrusion Porosimetry. The results showed that methylcellulose (MC), polycarboxylate superplasticizer (PC), and polyvinylpyrrolidone (PVP) could disperse CNFs in aqueous, but evident aggregations can be observed in the alkali solution. PC performed better than MC and PVP in alkali solutions, with 4.83% aggregation area of the whole image, 86% of 0–100 μm2 aggregations, and an average aggregation area of 87 μm2, beneficial from the comb-like structures. Dispersed CNFs can improve the 28-d flexural and compressive strength of the resulting geopolymer nanocomposite by 23% and 16%, respectively, and refine the pore structure through filling, bridging, and nucleation effects, decreasing the average pore size and porosity by 33% and 15%. This paper will contribute to the resourceful use of volcanic ash to reduce pollution and the higher reinforcement of CNFs in alkali-activated geopolymers.